Experimental study on noise mapping of split unit air conditioner system - M. H. A., Rasid; M. S. M., Sani (2014)
This paper presents the procedures and the results of noise source at the split unit air conditioner system. Noise in split unit air conditioning system is a frequent problem for the air conditioner manufacturers. Split unit air onditioners have an indoor unit and an outdoor unit connected by communication pipes. Noise can reduce the efficiency and performance of the air conditioner. In order to identify and analysis of noise at air conditioner system,experiment has been conducted using sound intensity mapping method.